Memetakan Lanskap Keilmuan Pendidikan Lingkungan: Tinjauan Bibliometrik Global dalam Perspektif Education for Sustainable Development (ESD) Tahun 2015–2025 - Abd Mannan; Emna Laisa; Nurul Shafarina (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
This study examines global developments in the academic fields of Islamic Education and Environmental Education as two intersecting disciplines during the period 2015–2025. The study aims to address the limitations of existing scholarly mapping that integrates ecological awareness with Islamic pedagogical frameworks, in light of the growing urgency of environmental ethics in global education. A bibliometric analysis was conducted on 2,119 Scopus-indexed journal articles, filtered by theme, language and document type, and visualised using VOSviewer. The results indicate a significant increase in academic interest in ecology-based Islamic education, particularly during the 2020–2024 period. The United States, Australia, and Spain are the main contributors, whilst Indonesia is beginning to play a strategic role in international collaboration. Emerging themes include eco-theology, green curricula, teacher training, and place-based learning. However, the representation of Islamic values in environmental education literature remains relatively low. Technological limitations and academic inequalities in developing countries also influence global participation. The originality of this research lies in its interdisciplinary approach, which systematically integrates two academic fields. Recommendations include strengthening cross-regional collaboration, integrating Islamic values such as tawhid and amanah into environmental education, and developing ecological literacy based on local spirituality to support sustainable education.